Monitoring Fenomena Urban Sprawl dan Prediksi Perubahan Tutupan Lahan Menggunakan Citra Landsat 8 di Kota Jambi - Arrafi, Muhammad; Salma, Nafisa Firyal (Geomedia Majalah Ilmiah dan Informasi Kegeografian, 2025)
Urban sprawl is a consequence of rapid and expansive urban growth, which has a significant impact on the environment and land use in suburban areas. This research aims to monitor urban sprawl phenomena and predict land cover changes in Jambi City using Landsat 8 satellite image data from 2016 to 2021. The results show an increase in the extent of built-up areas in Jambi City, especially in the districts of Kota Baru and Alam Barajo, in line with population growth in these areas. Predictions using the Molusce plugin indicate that built-up land will continue to increase, while non-built-up land will decrease over the next five to ten years. Furthermore, using a Directional Distribution approach, this research predicts that Jambi City's growth direction in 2026 and 2031 will be towards the southwest. Urbanization and the association between Muaro Jambi Regency and Jambi City play a role in the expansion of urban sprawl to the southwest.